Development of a documentation instrument for movement-orientated Mind-Body-Therapies taking the example of Eurythmy-Therapy. (June 2019) - Gerlach, Katharina; Recchia, Daniela Rodrigues; Büssing, Arndt
Highlights: 5-module documentation tool for movement-orientated Mind-Body-Therapies. Feasibility tested on Eurythmy Therapy Interventions. Outcomes showed initial sensitivity to change. Large effect size in observed movement qualities. Large correlation of observed movement qualities and patients' self-reported Quality of Life indicators. Abstract: Introduction: Movement orientated Mind-Body-Interventions become more popular. But there are no standardized documentation tools to show if an improvement in movement could correlate with an improvement in health. Yet systematic documentation is a vital requirement to their efficacy. Method: We developed a 5-module documentation structure including patients' perspective. Over a period of five months 11 therapists used the modules to document their treatments on 41 patients and evaluated their feasibility at hand a questionnaire. Results: 10 therapists and 37 patients met the inclusion criteria. In a documented variety of treatment concepts moderate to large effect size in observed movement qualities was found. Furthermore large correlation of observed movement qualities and patients' self-reported Quality of Life indicators could be shown. Conclusion: The modules were regarded feasible. Moreover, the outcomes showed initial sensitivity to change. They should therefore be tested in various movement orientated Mind-Body-Therapies.